Adventures of a guano digger in the Eastern Pacific - Chave, Richard Branscombe; Australian National University. Pacific Manuscripts Bureau (Canberra : Pacific Manuscripts Bureau, 1968)
In 1871, when Starburk Island in the Eastern Pacific was under lease from the British Government to Houlder Bros., of London, Chave, then 22, was in charge of a team of three Europeans and 50 Rarotongans who were working the island for its guano. When provisions began to run low, and there was no sign of a brig which was to bring replenishments, Chave and three Rarotongans set off in a large boat to try to reach Malden Island, 120 miles away, which was being worked for guano by a Melbourne company. After becoming lost and surviving a capsize, the party reached Penrhyn Island, several hundred miles in the opposite direction. Later, Chave and a Penrhyn Islander tried to sail back to Starbuck Island, but again Chave became lost and he and his companion finally drifted to an uninhabited island, which proved to be Suwarrow Atoll, where they lived for two years before being rescued. Chave's narrative gives a vivid account of his adventures up to a point where he and his compannion had been on Suwarrow for about nine months. For further details, see Pambu for November, 1968, pp. 5-9; and January, 1969, pp. 6-9.
Guide to collections of manuscripts relating to Australia
Microfilm copy of original held by Alexander Turnbull Library, Wellington, New Zealand.
Keywords: Chave, Richard Branscombe; Guano industry -- Employees -- Biography; Guano industry -- Line Islands; Suwarrow Atoll (Cook Islands).; Penrhyn (Cook Islands)